Post-trial obligations - DOI: 10.3395/reciis.v2.Sup1.210en - Doris Schroeder (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
In its essence, post-trial obligations describe a duty by research sponsors to provide a successfully tested drug to research participants who took part in the relevant clinical trials after the trial has been concluded. In some instances, this duty is extended beyond the research participants. This article is divided into three main parts. The first part outlines the legal basis for post-trial obligations by looking at international guidelines, including those issued by the World Medical Association. National legislation is exemplified through resolutions and guidelines issued by Brazil and South Africa respectively. The second part analyses the ethical foundation for post-trial obligations, in particular the attempt to minimize exploitation of research subjects. The third part raises obstacles and challenges for the implementation of post-trial obligations. The jury is still out on whether post-trial obligations in the form of access to drugs for clinical trial participants is the best, or even a good way, to avoid exploitation in medical research.